2009
DOI: 10.1089/cap.2008.074
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine Treatment in Adolescents with Attention-Deficit/Hyperactivity Disorder

Abstract: Maintenance of benefit with atomoxetine hydrochloride in adolescents with ADHD, NCT00191035.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The mean change in math grade was from C to B-. However, no significant improvement occurred in English, science and social studies grades with any dose of atomoxetine [104]. Pelham and colleagues observed statistically nonsignificant increases versus placebo in GPA (1.6-1.9) with IR-MPH and pemoline [105].…”
Section: Grade-point Average (Gpa)mentioning
confidence: 97%
See 1 more Smart Citation
“…The mean change in math grade was from C to B-. However, no significant improvement occurred in English, science and social studies grades with any dose of atomoxetine [104]. Pelham and colleagues observed statistically nonsignificant increases versus placebo in GPA (1.6-1.9) with IR-MPH and pemoline [105].…”
Section: Grade-point Average (Gpa)mentioning
confidence: 97%
“…No effect on math scores was observed and results were limited by the lack of a control arm. Forty weeks later, approximately half of the acute gains in total achievement score had eroded, with a trend for better reading scores in the higher (1.4 mg/ kg/day), but not the lower dose group (0.8 mg/kg/day) [104].…”
Section: Achievement Testingmentioning
confidence: 99%
“…No differences were observed when participants adopted either a slow or fast titration schedule, and significant improvements to ADHD symptoms, life participation, family functioning, academic achievement, and some risky behavior ratings were observed after both titration schedules (Table 2). 30,31 In relation to one versus two daily doses, Waxmonsky et al found that one daily dose was superior to two daily doses in behavior and impairment ratings, where after eight weeks of treatment, significant benefits were observed in some of the measures only in those who took one daily dose (Table 2). 19,20 Additionally, Waxmonsky et al assessed participants every fortnight and found that improvements in parent-rated behaviors improved from the commencement of treatment (within the first fortnight) when one dose per day was taken, while benefits with two daily doses were first noticed halfway through the eight-week treatment period.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the short-term reports, the longer-term studies compared atomoxetine to other treatments (stimulants32 and methylphenidate23,24) and to placebo arms and combined atomoxetine treatment with other treatment modalities (motivational interviewing plus cognitive behavior therapy33 and psychoeducation for parents34). Atomoxetine dosing was examined also in relation to fast versus slow titration35,36 and compared low doses (0.8 mg/kg/d) to higher doses (1.4 mg/kg/d) 30,31. Cohorts used for comparisons included healthy controls and participants with ADHD with comorbid dyslexia (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…When atomoxetine is administered once daily, some evidence suggests that morning dosing may be more efficacious, but evening dosing may be more tolerable [84]. In adolescents, doses in the higher ranges have been associated with greater long-term efficacy [85]. Because atomoxetine has been rarely associated with acute suicidality [86], it has been given a 'black box' warning.…”
Section: Adhd Treatmentsmentioning
confidence: 99%